Problems of portal users behaviour specification - Lupeikienė, Audronė; Čaplinskas, Albertas; Dzemyda, Gintautas (Lietuvos matematikos rinkinys, 2009)
This paper is a position paper, so it presents not well-established scientific truths but remarks and notices on the phenomena and their generalisations. The paper asserts that current portal design practices are not sound, advocates for an explicit specification of the assumptions about the predicted users’ behaviour, and requires that a specification language to formulate such the assumptions should be based on the formalism of temporal logic of actions.
Keywords: portal; user behaviour specification; temporal logic of actions